2014
DOI: 10.1371/journal.pntd.0003156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid Diagnostic Test for Yaws Infection in a Community Surveillance Setting

Abstract: Yaws is a non-venereal treponemal infection caused by Treponema pallidum ssp. pertenue. The WHO has launched a worldwide control programme, which aims to eradicate yaws by 2020. The development of a rapid diagnostic test (RDT) for serological diagnosis in the isolated communities affected by yaws is a key requirement for the successful implementation of the WHO strategy. We conducted a study to evaluate the utility of the DPP test in screening for yaws, utilizing samples collected as part of a community preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 12 publications
4
38
0
Order By: Relevance
“…This study showed a lower sensitivity and specificity compared to the only prior evaluation of this assay [27], suggesting that the test is most useful for confirmation in patients with highly active clinical disease [26]. This rapid screening test does not perform as well in patients with latent disease nor useful in areas with low prevalence [26]. The search for a cost-effective rapid screening test in asymptomatic patients remains to be seen, however, does serve a useful function in post-mass drug administration monitoring.…”
Section: Diagnosismentioning
confidence: 59%
See 2 more Smart Citations
“…This study showed a lower sensitivity and specificity compared to the only prior evaluation of this assay [27], suggesting that the test is most useful for confirmation in patients with highly active clinical disease [26]. This rapid screening test does not perform as well in patients with latent disease nor useful in areas with low prevalence [26]. The search for a cost-effective rapid screening test in asymptomatic patients remains to be seen, however, does serve a useful function in post-mass drug administration monitoring.…”
Section: Diagnosismentioning
confidence: 59%
“…The sensitivity of the ChemBio DPP syphilis screen was correlated to higher RPR titers, having a sensitivity of 92.0% for an RPR titer of >1:16. This study showed a lower sensitivity and specificity compared to the only prior evaluation of this assay [27], suggesting that the test is most useful for confirmation in patients with highly active clinical disease [26]. This rapid screening test does not perform as well in patients with latent disease nor useful in areas with low prevalence [26].…”
Section: Diagnosismentioning
confidence: 63%
See 1 more Smart Citation
“…Interest in yaws has been revived by the finding that azithromycin is a highly effective treatment of both primary and secondary yaws 2. Clinical diagnosis alone of primary yaws is unreliable, but a point-of-care test has been shown to be of value 3. This test provides a result analogous to a T. pallidum particle agglutination assay (Figure 2
Figure 2.Combined treponemal and nontreponemal rapid diagnostic test for yaws.
, line 1) and a rapid plasma reagin (RPR) assay (Figure 2, line 2).…”
mentioning
confidence: 99%
“…Progress toward the elimination of transmission could be monitored by means of point-of-care serologic surveys for latent yaws in children. 4 Finally, as with mass drugadministration programs for controlling and eliminating other infectious diseases, maintaining high levels of community participation in treatment and monitoring will be essential. Azithromycin uptake by 80% or more of eligible community participants, as Mitjà et al report in Papua New Guinea, with continued targeted community treatment will be critical if local elimination and, ultimately, global eradication of yaws are finally to be realized.…”
mentioning
confidence: 99%